Chemosynthetic symbionts of marine invertebrate animals are capable of nitrogen fixation - Petersen, Jillian M.; Kemper, Anna; Gruber-Vodicka, Harald; Cardini, Ulisse; van der Geest, Matthijs; Kleiner, Manuel; Bulgheresi, Silvia; Mußmann, Marc; Herbold, Craig; Seah, Brandon K.B.; Antony, Chakkiath Paul; Liu, Dan; et al. (Nature microbiology, 2016)
Chemosynthetic symbioses are partnerships between invertebrate animals and chemosynthetic bacteria. The latter are the primary producers, providing most of the organic carbon needed for the animal host's nutrition. We sequenced genomes of the chemosynthetic symbionts from the lucinid bivalve Loripes lucinalis and the stilbonematid nematode Laxus oneistus . The symbionts of both host species encoded nitrogen fixation genes. This is remarkable as no marine chemosynthetic symbiont was previously known to be capable of nitrogen fixation. We detected nitrogenase expression by the symbionts of lucinid clams at the transcriptomic and proteomic level. Mean stable nitrogen isotope values of Loripes lucinalis were within the range expected for fixed atmospheric nitrogen, further suggesting active nitrogen fixation by the symbionts. The ability to fix nitrogen may be widespread among chemosynthetic symbioses in oligotrophic habitats, where nitrogen availability often limits primary productivity. The chemosynthetic symbionts of the bivalve Loripes lucinalis and nematode Laxus oneistus are found to encode nitrogen fixation genes, with evidence for active nitrogen fixation.